The Compassionate Engagement and Action Scale for Youths: psychometric properties in a clinical psychiatric Swedish sample - Wallin, Linda; Svedin, Carl-Göran; Wiberg, Marie; Dennhag, Inga (Frontiers in Psychology, 2026)
BackgroundCompassion contributes to wellbeing and serves as a protective factor against mental health problems in young people. The Compassionate Engagement and Action Scale for Youth—Swedish version (CEASY-SE) is a self-report questionnaire that assesses compassion across six competencies, organized into three scales: Self-Compassion, Compassion for Others, and Compassion from Others. While previously validated in a Swedish school sample, its applicability in clinical psychiatric populations remains unexplored. This study aimed to evaluate the psychometric properties of CEASY-SE in a clinical psychiatric sample of Swedish youth aged 16–22.MethodsA cross-sectional study was conducted, collecting self-reported data from young people (N = 355) receiving care in child and adolescent psychiatry and primary care. We assessed the CEASY-SE's factor structure, reliability, and validity (internal consistency, convergent, divergent, construct, and criterion-related validity). Sex and age differences were also analyzed, along with comparisons of total scores across diagnostic groups.ResultsConfirmatory factor analyses supported a two-factor model within each of the three scales. Internal consistency was good to excellent across all scales (α ranging from 0.75 to 0.92), except for the Self-Compassion Engagement subscale among males (α = 0.62; ω = 0.60). Convergent and divergent validity were satisfactory. Among the three CEASY-SE scales, Self-Compassion showed the strongest correlations with mental health outcomes. Sex differences primarily affected Compassion for Others, and a sex-by-age interaction was found for both Compassion for Others and Self-Compassion. A total score of 40 was associated with an 8.41-fold increase in the predicted probability of depression symptoms compared to a score of 100. The lowest scores were found among patients with eating disorders and depression.ConclusionsThe CEASY-SE demonstrates acceptable to excellent psychometric properties in a clinical psychiatric sample of youth. It is a promising tool for clinicians and researchers to assess and promote compassion in young people, with potential relevance for interventions aimed at improving mental health outcomes.